Las posturas al interior del Partido Acción Nacional a propósito de la represión estudiantil de 1968 - Tania Hernández Vicencio (Nuevo mundo - Mundos Nuevos, 2017)
The analysis of student repression of October 2, 1968, at Mexico has been the center of much of the discussions on the development of social and leftist movements, the transformation of the political system and changes in the state's relationship with the society. However, it´s necessary to analyze how this unfortunate event impacted the social and political right-wing organizations, showing the different positions against the government and even experienced several positions to its interior, like to this happened in the National Action Party. This paper analyzes the way the student repression impacted the life into the party, identifying the different positions, conflicts and strategies of several of its leaders.